Respuesta de 14 cultivares de melon (Cucumis melo L.) al Cletodim - Loria Quiros, C.L.=700 1 Herrera Murillo, F.
(Es, En)
Ilus., 16 ref.
Keywords: CUCUMIS MELO; HERBICIDAS; MALEZAS; ESCARDA; EVALUACION; COSTA RICA; CLETODIM; AGRONOMIA MESOAMERICANA